KONTRIBUSI NUHAT DALAM PENGEMBANGAN STUDI HADIS (Tela’ah atas I’rab al-Hadis al-Nabawi Karya Abu al-Baqa’ al-’Ukbari) - Yahya, Muhammad (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2014)
In this article the author elaborates the works of Abu al-Baqaâ€™ al-â€™Ukbari, Iâ€™rÄb al- Hadis al-NabawÄ«. The appearance of this work is effected by the concerns of nuhat to the phenomenon of lahn in matan. There are a number of 125 transmitters that he criticize on nahwiyah perspectives. Of these 10 are women. Not all elements of the structure of matan he elaborates, only certain words in the matan deemed or alleged to have or contain ambiguity aroused assumptions of lahn. The work of al-â€™Ukbari is thought as the first work in the corpus studies of Hadis.